Job Satisfaction And Employee Performance In Local Government: A Case Study Of Kyankwanzi District, Uganda - Amos Ofumbi; Edmand Bakashaba (Student's Journal of Health Research, 2022)
Background: This study was about Job Satisfaction and Employee Performance in Local Government using  Kyankwanzi District by  establishing the link between promotion and employee attitude, working conditions and employee attendance, the relationship with supervisor and duration in service. Methodology: The researcher adopted a correlational, descriptive and cross-sectional survey design. Both qualitative and quantitative approaches were used. A sample of 63 respondents was selected using Krejcie & Morgan's (1970) table from a population of 75. The researcher employed simple random sampling, purposive sampling, quota sampling and convenience sampling to select respondents who participated in the study in order to eliminate bias. The instruments of data collection the researcher used include questionnaire, interview guide and documentary review. Results: The study established that male respondents dominated the study with 70% response followed by their female counterpart who comprised of 30%. Also the findings revealed that there was a relationship between job satisfaction (independent variable) and employee attendance (dependent variable). It shows a correlation coefficient of r= 0.840. This implies that there is a significant (0.000) positive relationship between job satisfaction and employee attendance at Kyankwanzi District Local Government. In conclusion, the study has dealt with inferential statistical analysis and interpretations. The researcher investigated the existence of an association between the task grades and the responses of the employees for questionnaire statements. This was done using a null hypothesis and the alternative hypothesis. Recommendations: Future studies should be centered on staff training and poor service delivery in newly elevated cities focusing on political manipulation, corruption and lack of accountability and transparency.